Hovden Cannery Bridge - Ed Ricketts, Junior:::Creator::::::::::::
Wooden trestle bridge for Hovden's Cannery that was next to Pacific Biological Laboratory at 800 Cannery Row. Structure was used to bring fish to the cannery before hoppers and pipes were built.